The Portrait of Public Relations Strategic Planning (2023)
Strategic planning is a concept for building a specific and comprehensive work plan. The concept importance  of the strategic planning in public relations activities is to facilitate the preparation and analysis of a series of work plans to be carried out. The purpose of this paper is to observe and analyze a series of public relations strategic planning concepts from several pioneers, as Jhon Marston (1963), Cutlip, Center, Broom (2000), Ronald D.Smith (2002), Anne Gregory (2000). The writing method is a qualitative descriptive format. The result of observing is the concept development of strategic planning which was born based on the criticism and development of previous concepts. Making systematic strategic planning, needs to be done  by public relations practitioners to facilitate work operations. There are many more specific strategic planning aproaches, although there is no single approach, the essence of planning according to certain elements must exist. This paper is expected to enrich academics’ knowledge, especialy communication science students and public relations practitioners in making effective and comprehensive strategic planning based on scientific concepts and theory.